Interventions to prevent the onset of frailty in adults aged 60 and older (PRAE-Frail): a systematic review and network meta-analysis - Eidam, Annette; Durga, Jane; Bauer, Jürgen M.; Zimmermann, Samuel; Vey, Johannes; Rapp, Kilian; Schwenk, Michael; Cesari, Matteo; Benzinger, Petra (European geriatric medicine, 2024)
To analyze the effectiveness of different interventions in preventing frailty onset in older adults.
Veröffentlicht: 26. Juli 2024
Gesehen am 15.01.2025